Methods for the Detection of Peptidylarginine Deiminase (PAD) Activity and Protein Citrullination - Hensen, Sanne M. M. (The American Society for Biochemistry and Molecular Biology, 2014)
The post-translational conversion of peptidylarginine to peptidylcitrulline, a process also known as citrullination, is catalyzed by the enzyme family of peptidylarginine deiminases (PADs) and has been demonstrated to be involved in many physiological processes, including the regulation of gene expression. In addition, citrullination has been shown to be associated with several diseases, such as cancer, multiple sclerosis, rheumatoid arthritis, and Alzheimer's disease. To get more insight into the role of PAD enzymes and citrullination in both health and disease, experimental strategies to study PAD activity and to characterize citrullinated proteins in complex biological samples are crucial. Here, we describe the chemical, proteomic and antibody-based procedures that are currently available and discuss their applicability for the analysis of complex samples. The methods that have been developed can be used to provide more insight in the substrate specificity of PAD enzymes. Because the evidence that PADs play a pathophysiological role in the diseases mentioned above is increasing, they become attractive targets for therapeutic interventions. More knowledge of PAD specificity and the availability of reliable, high-throughput assays for PAD activity will facilitate the development of highly specific PAD inhibitors.